BA Students’ Perceptions of Standardized English Tests - Vez López, Enrique; Molina Muñoz, Karla Elizabeth; Sánchez Hernández, Diana Iveth (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This research examines the perceptions of a group BA students of English a s a foreign language regarding standardized English tests at a school of languages in the estate of Veracruz, Mexico. In this school program, all students take the same evaluations in order to assess their English proficiency level. This research study made use of a questionnaire containing both open-ended and close-ended questions to examine students’ viewpoints about tests design, validity, fairness and reliability. Numeric data as well as the participants’ viewpoints and comments were used to support and present the findings. By analyzing the students’ questionnaire answers, it was possible to identify whether the participants thought this type of assessment was fair, reliable, and valid in evaluating their proficiency level. In addition, this research helped identify weaknesses and strengths of standardized exams in this context.